Interplay of Performance‐Limiting Nanoscale Features in Cu2ZnSn(S, Se)4 Solar Cells. Issue 21 (22nd September 2020) - Ritzer, Maurizio; Schönherr, Sven; Schöppe, Philipp; Larramona, Gerardo; Choné, Christophe; Gurieva, Galina; Johannes, Andreas; Ritter, Konrad; Martínez-Criado, Gema; Schorr, Susan; Ronning, Carsten; Schnohr, Claudia S.
Abstract : Highly performing kesterite‐based Cu2 ZnSn(S, Se)4 (CZTSSe) thin‐film solar cells are typically produced under Cu‐poor and Zn‐rich synthesis conditions. However, these processing routes also facilitate the formation of secondary phases as well as deviations from stoichiometry, causing intrinsic point defects. Herein, the local composition of CZTSSe absorbers prepared with different nominal cation concentrations is investigated by applying energy dispersive X‐ray spectroscopy and synchrotron X‐ray fluorescence spectroscopy at the nanoscale to cross‐sectional lamellae. The findings confirm the formation of ZnS(Se) secondary phases, whose presence, number, and dimension strongly increase with the reduction of the nominal Cu and increment of the nominal Zn content. Furthermore, the local compositions of the CZTSSe phase within the absorber reveal strong variations, leading to collateral and multiple off‐stoichiometry types of the kesterite phase in the absorber, which cause different intrinsic point defects. Therefore, the off‐stoichiometry type determined from the integral composition does not represent the complete true picture of this complex material system. Accordingly, the correlation of integral composition with electrical properties or conversion efficiency may be misleading. Overall, the approach provides new experimental insights into the nanoscale relationship among local compositional fluctuations, off‐stoichiometry types, and secondary phases in these promising photovoltaic materials. Abstract : Electron and X‐ray‐based fluorescence analysis of Cu2 ZnSn(S, Se)4 (CZTSSe) thin films reveal the presence of ZnS(Se) secondary phases. The presence causes a substantial difference of the intended and realized CZTSSe absorber composition, which, in fact, remains Cu‐poor and Zn‐rich. Furthermore, fluctuations of the local cation concentrations lead to different types of intrinsic defects, which strongly affect the local electronic properties.